Sustainable development in western China managing people, livestock and grasslands in pastoral areas - Brown, Colin G.; Waldron, Scott A.; Longworth, John W. (John William), 1940-; Edward Elgar Publishing (Cheltenham [England] ; Northampton, Mass. : Edward Elgar, 2008)
This study provides a guide to & analysis of the intricate web of policies & institutions that now impact on grassland degradation & sustainable development in China's pastoral region. It also reveals broader insights into how China grapples with complex ecological & livelihood problems as it rapidly modernises & develops.
Romance, reality and reformation of China's grasslands -- Grassland systems and challenges -- Managing institutions -- Managing grassland policies -- Managing structures -- Managing livestock systems -- Managing markets -- Managing people -- Unique problems--unique solutions.
Includes bibliographical references (p. 272-277) and index.
Keywords: Range management -- China; Grasslands -- China -- Management; Range policy -- China; Livestock -- Economic aspects -- China; Livestock -- Government policy -- China; Rural development -- Government policy -- China; Sustainable development -- China; Electronic books